(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Measurement and Instrumentation fundamentals are introduced to electrical and mechanical engineering students via unique joint course for Electrical and Mechanical Engineering Programs of Purdue University at Fort Wayne Campus. The course has a laboratory component that engages students with practice and illustrates how to apply theory. The students are grouped to conduct experiments in a multidisciplinary format. It has been observed that this type of unique joint course motivates students to solve engineering problems from different perspectives and improves teamwork.